Somatic embryogenesis from the axillary meristems of peanut (Arachis hypogaea L.) - Singh, Shweta; Hazra, Sulekha (Plant Biotechnology Reports, 2009)
Developmental anomalies in the plumule meristem of peanut (Arachis hypogaea L.) somatic embryos resulted in poor shoot differentiation and reduced plant recovery. Existing meristems with caulogenic potential have never been tested for embryogenesis in peanut. The present experiment was designed to test the mature zygotic embryo axis derived plumule with three meristems for somatic embryogenesis. Embryogenic masses and embryos developed from the caulogenic meristems in the axils. Exposure of 2 weeks in primary medium with 90.5 A mu M 2,4-D suppressed the shoot tip differentiation temporarily which then regained the ability to form the shoot on withdrawal of 2,4-D. Exposure of 4 weeks in primary medium with 90.5 A mu M 2,4-D suppressed the shoot tip differentiation irreversibly. No shoot formation was noted from the tips in any of the cultures which were in secondary medium with 13.6 A mu M 2,4-D. Development of somatic embryos directly from axillary meristems was confirmed histologically. Conversion frequency of these embryos was 11%. Thus, in this report, we describe a method to obtain somatic embryos from the determined organogenic buds of the axillary meristem, by culturing the nodal explant vertically on embryo induction medium. It also displays the possibility of obtaining both embryogenic and organogenic potential in two parts of the same explant simultaneously. The possibility of extending this approach for genetic transformation in in vivo system through direct DNA delivery or Agrobacterium injection in meristems can also be explored. Using Agrobacterium rhizogenes, we have demonstrated the possibility of gene transfer in the axillary meristems of seed-derived plumule explant.
Keywords: Apical meristem; Axillary meristem; Mature zygotic embryo axis; Peanut; somatic embryogenesis